1- and 2- dimensional (1 D/2 D) hydroxyapatite nanocrystals: A deep insight into synthesis strategies and multidimensional applications - Kesarwani U.; Basu B.; Dubey A.K. (My University, 2025)
Recently, one- and two- dimensional (1- and 2- D) hydroxyapatite (HA) nanocrystals gained remarkable attention for their potential multifold performance in diverse areas such as, bone tissue engineering, drug delivery, water purification, dental applications, catalysis, biocoatings, fire-resistant HA textile, security printing, anticounterfeiting paper, fire alarm wall paper, HA macro ribbon fiber, Li-S battery, and hemostatic aerogel, etc. The present article critically and comprehensively reviews various synthesis routes for the development of different morphologies of HA nanocrystals such as nanorods, nanoplates, nanowires, nanofibers, nanotubes, nanoneedles, nanowishkers, nanobelts, nanoribbons and nanosheets, with a focus to understand the process science. Moreover, the role of various experimental parameters such as hydrothermal temperature and time, nature and concentration of organic additives, pH of precursor solution, and elemental doping on size, morphology, aspect ratio, crystallinity and state of agglomeration of HA nanocrystals are thoroughly discussed. Further, the systematic discussion has also been made on each type of application of HA nanocrystals, with special emphasis on several essential physical and experimental parameters to achieve the performance of HA nanocrystals for bone tissue engineering, drug delivery, water purification etc. Overall, this study critically analyzed various synthesis routes to develop 1- and 2- D HA nanocrystals and their multifaceted applications. © 2024 Elsevier Ltd